(untitled) (Al-Academy, 2021)
This research is represented by exploring the experience of "the theater of the oppressed" by (Augusto Boal) as an experiment that represents a different aesthetic pattern in the presentation of theatrical performance which is in contrast with the Aristotelian and Brechtian patterns, and as a result of the increasing problems of the individual in societies according to his needs and an attempt to express the suffering of human and the loss of his rights in general.The research also tries to uncover the power of identification and the alienation of existence in the theater of the oppressed as that power, with its diversity of legal, legitimate, religious, political, economic and social capabilities has become a burden instead of being a help because of the wrong policies in dealing with the problems of the individual, as the theater of the oppressed tries to uncover the hidden in the authority of identification and revealing the alienation of the human existence that imposed on individual. The researcher tried to present a detailed narration in four chapters, the first chapter of which represents the definition of the research problem, which is the question about what the authorities are, their multiplicity and their fusion in the alienation of the human existence in the theater of the oppressed, as well as the importance of the research as it constitutes a milestone in the nature of identifying the elements of the conflict for the recipient to be a protagonist in addition to the characters of the play. And the purpose of the research, which was about reveal those authorities and focus on how to confront them and budge those identifications to prove their presence, as the research’s limits were determined spatially in Iraq, temporally in (2015) and objectively, as it revolved around the axis of identification authority and the alienation of existence in the theater of the oppressed.The second chapter included two topics, the first of which focused on (the authority of identification and the alienation of existence - philosophical introductions "), while the second topic focused on (the references of discourse in the theater of the oppressed), and then previous studies and indicators of the theoretical framework.The third chapter, which is the chapter of procedures, as it centered on the research community, which was chosen according to the intentional method as well as the research sample, that was represented by the text of the play "Falak Aswad" (gloomy distress) by the Iraqi writer (Ali Abd al-Nabi al-Zaidi), and the descriptive research approach in analyzing the sample as well as the indicators and the analyzing of research’s sample.As for the fourth chapter, it focused on the research results, discussions, conclusions, proposals and recommendations, and then the sources and the research abstract in English.